The Epidemiological Analysis of Pseudorabies Virus and Pathogenicity of the Variant Strain in Shandong Province - Ren, Qinghai; Ren, Hongwei; Gu, Jinyuan; Wang, Jin; Jiang, Luyao; Gao, Song (Frontiers in Veterinary Science, 2022)
Pseudorabies (PR) is a disease that is seriously endangering the pig industry in China. To understand the current prevalence of pseudorabies virus (PRV) in Shandong Province, China, 19,292 serum samples were collected from 16 locations in Shandong from 2018 to 2020. The gE antibody was detected by enzyme-linked immunosorbent assay. Ninety-seven suspected cases of PRV infection were collected from sick pigs vaccinated with Bartha-K61 to isolate PRV. The results showed that the average positive rate of the PRV gE antibody decreased from 38.20% in 2018 to 18.12% in 2020, but there was a high positive rate in sows. The isolation rate of PRV was 13.40% (13/97), and four strains were purified through plaque assay (named PRV-SD1, PRV-SD2, PRV-SD3, and PRV-SD4). The homology and genetic evolution of four PRV strains based on gE, gC, gI and TK genes were analyzed and showed that these four strains shared more than 99.0% nucleotide homology with the variant PRV XJ5 strain, and they clustered in the same sub-branch with the domestic variant PRV strains, including JS-2012 and XJ5. Furthermore, the pathogenicity of the isolated variant strain was assessed by intranasal infection of 16-week-old pigs with 1 mL PRV-SD1 strain. The results of the animal experiment demonstrated that the PRV-SD1–infected pigs exhibited obvious clinical symptoms as early as two days post inoculation (dpi), and all infected pigs died within 1 week. The severe hyperemia of meninges and swelling of lungs and tonsils were observed. Histopathology analysis showed the obvious lymphocytes necrosis of tonsils, interstitial pneumonia, and viral encephalitis. Many positive staining cells were observed in tonsils and brains through immunohistochemistry staining assay. Viral shedding in oropharyngeal and rectal swabs were detected at 2 dpi, reached a peak at 3 dpi, and then gradually decreased. The detection of viral loads in the tissues showed that tonsils had the highest virus titer, further proving it may be the target organ of variant PRV infection. In conclusion, variant PRV strains were still highly prevalent in Shandong Province, and they had a strong pathogenicity in pigs.